أدائية الصورة البيانية في ديوان ابن الخياط الدمشقي (ت517هـ) - حليم علي إسراء (Journal of College of Education, 2020)
The ancients didn’t overlook the performance of the graphic image and its effect on the recipients, because the metaphoric language was present within the Qur’an and poetry, especially poetry, so poetry isn’t barren of these images and its performance lies therein casting intent in its templates gives an aesthetic value and a convincing value that might not are if the speaker was used and therefore the poet has resorted to explaining his words with these images. Ibn Al-Khayyat’s divan had not been studied from this side, so we found a glimpse of this performance in his office, and that we completed a search plan on three topics that came (the first within the performance of the simulated image, and therefore the second within the performance of the metaphor, The last within the performance of the image isn’t explicit) and the work wasn’t statistical, but rather models chosen randomly by the researcher to understand the extent of this poet’s use of those images, and that i didn’t meet all the graphic images in Arabic rhetoric, but was limited to the common ones.